Impulsive Buying on the Member of Online Shopping Community: The Role of Self-regulation - Fathin Fadhilah; Ni Wayan Sukmawati Puspitadewi (Indonesian Psychological Research, 2024)
Impulsive buying has become a major issue among the younger generation. Identifying factors that can prevent impulsive buying is crucial for promoting both mental and financial well-being. This study aims to explore the relationship between self-regulation and impulsive buying among members of online shopping communities. We focused on several Telegram communities consisting of people who often shop online only during big promotions. This correlational quantitative research involved 100 participants, selected using a convenient sampling technique. Data analysis using Pearson product moment correlation analysis showed a coefficient value of -0.590 and R² = 0.348 with a significance value of 0.000 (p < 0.05). This result indicates that there is a medium-strength negative relationship between self-regulation and impulsive buying. In other words, as self-regulation increases, impulsive buying decreases. These findings highlight the importance of developing self-regulation skills to reduce impulsive buying behavior, which can contribute to better mental and financial health among young people who are active in online shopping.